Comparison of anxiety, pain, and quality of life in individuals with mild or moderate malocclusion between conventional fixed orthodontic treatment versus Invisalign: a randomised clinical trial - Yasemin Tunca; Yesim Kaya; Murat Tunca; Sıddık Keskin (BMC, 2024)
Abstract Background We evaluated anxiety, pain, and oral-health-related quality of life in individuals treated with conventional fixed appliances (Group A) and clear aligners (Group B) for moderate malocclusion during the initial phase of orthodontic treatment. Methods Sixty individuals, separated into Group A (n = 30) and Group B (n = 30), were included in the study. They completed the Anxiety Levels, Oral Health Impact Profile-14, and Oral Health Related Quality of Life - United Kingdom/Surveys after the application of attachments on days 0 (T1), 10 (T10), and 20 (T20). Their pain levels were evaluated with the Visual Analogue Scale on days 0, 2, and 6 in the 2nd and 6th hours and on the 1st, 3rd, 7th, 14th, and 21st days. Results Per the VAS questionnaire, pain levels in the 2nd hour, 6th hour, 1st day, and 3rd day were significantly lower in Group B than in Group A. In the OHIP-14 survey results, the comparison between Group A and Group B showed a significant difference only on the 1st day. The STAI and OHRQoL-UK survey results did not differ significantly between the groups. Conclusions We found no significant difference between the two groups in terms of anxiety levels, and pain among individuals in Group A was higher than in Group B only at the beginning of the treatment. No significant differences were observed in terms of individuals' quality of life. Trial registration NCT06133296 (retrospectively registered)- Registration Date:15/11/2023.